Design and Analysis of Vehicle Anti-Lock Braking System with Fuzzy Logic, Bang-Bang and PID Controllers - Lakhemaru, Prashant; Adhikari, Surya Prasad (Himalayan Journal of Applied Science and Engineering, 2022)
In this study, a mathematical model of Anti-Lock Braking System (ABS) has been developed and simulated in MATLAB/Simulink environment using bang-bang, fuzzy logic and PID controllers. The controllers were used to control the braking force to be applied based on various parameters like relative slip, road condition and coefficient of friction between road and tire. The simulated result was compared and analyzed. The simulation result showed that a PID controller would take 9.665 seconds to stop the vehicle at the distance of 434.902 ft at an initial velocity of 88 ft/s. The Fuzzy Logic, Bang-Bang and no controllers offered 935.298 ft at 16.76 seconds, 696.996 ft at 13.751 seconds and 1421.327 ft at 24.217 seconds, respectively for the same initial velocity and road surface. From analysis, it was concluded that the PID controller had better performance compared to fuzzy logic and bang-bang controllers for application of ABS in a vehicle.